Elevated Plasma Levels of Drebrin in Glaucoma Patients With Neurodegeneration - Gan, Yi-Jing; Fang, Ai-Wu; Liu, Chang; Liu, Bai-Jing; Yang, Feng-Mei; Guan, Ji-Tian; Lan, Chun-Lin; Dai, Xiao-Dan; Li, Tong; Cao, Ying; Ran, Yun; Gong, Xian-Hui; et al. (Frontiers in Neuroscience, 2019)
Glaucoma is an optic neuropathy characterized by progressive degeneration of retinal ganglion cells (RGCs). Aberrations in several cytoskeletal proteins, such as tau have been implicated in the pathogenesis of neurodegenerative diseases, could be initiating factors in glaucoma progression and occurring prior to axon degeneration. Developmentally regulated brain protein (Drebrin or DBN1) is an evolutionarily conserved actin-binding protein playing a prominent role in neurons and is implicated in neurodegenerative diseases. However, the relationship between circulating DBN1 levels and RGC degeneration in glaucoma patients remains unclear. In our preliminary study, we detected drebrin protein in the plasma of glaucoma patients using proteomic analysis. Subsequently, we recruited a total of 232 patients including primary angle-closure glaucoma (PACG), primary open-angle glaucoma (POAG) and Posner-Schlossman syndrome (PS) and measured its DBN1 plasma levels. We observed elevated DBN1 plasma levels in patients with primary glaucoma but not in patients with PS compared to nonaxonopathic controls. Interestingly, in contrast to tau plasma levels increased in all groups of patients, elevated drebrin plasma levels correlated with retinal nerve fiber layer defect (RNFLD) in glaucoma patients. To further explore the expression of DBN1 in neurodegeneration, we conducted experiment of optic nerve crush (ONC) models, and observed increased expression of DBN1 in the serum as well as in the retina and then decreased after ONC. This result reinforces the potentiality of circulating DBN1 levels are increased in glaucoma patients with neurodegeneration. Taken together, our findings suggest that circulating DBN1 levels correlated with RNFLD and may reflect the severity of RGCs injury in glaucoma patients. Combining measurement of circulating drebrin and tau levels may be a useful indicator for monitoring progression of neurodegenerative diseases.